Extracorporeal Carbon Dioxide Removal Using a Renal Replacement Therapy Platform to Enhance Lung-Protective Ventilation in Hypercapnic Patients With Coronavirus Disease 2019-Associated Acute Respiratory Distress Syndrome - Husain-Syed, Faeq; Birk, Horst-Walter; Wilhelm, Jochen; Ronco, Claudio; Ranieri, V. Marco; Karle, Bianka; Kuhnert, Stefan; Tello, Khodr; Hecker, Matthias; Morty, Rory E.; Herold, Susanne; Kehl, Oliver; et al. (Frontiers in Medicine, 2020)
Coronavirus disease 2019 (COVID-19)-associated acute respiratory distress syndrome (ARDS) is associated with high mortality. Lung-protective ventilation is current standard of care in patients with ARDS, but it might lead to hypercapnia, which is independently associated with worse outcomes. Extracorporeal carbon dioxide removal (ECCO2R) has been proposed as an adjuvant therapy to avoid progression of clinical severity and limit further ventilator-induced lung injury but its use in COVID-19 has not been described yet. Acute kidney injury requiring renal replacement therapy (RRT) is common among critically ill COVID-19 patients. In centers with available dialysis, low-flow ECCO2R (<500 mL/min) using RRT platforms could be carried out by dialysis specialists and might be an option to efficiently allocate resources during the COVID-19 pandemic for patients with hypercapnia as the main indication. Here, we report the feasibility, safety and efficacy of ECCO2R using a RRT platform to provide either standalone ECCO2R or ECCO2R combined with RRT in four hypercapnic patients with moderate ARDS. A randomized clinical trial is required to assess the overall benefit and harm.